Effects of Gd3+: Ag co-doping on structural and magnetic properties of lead tellurite glass ceramics. Issue 1 (January 2016) - Bosca, M.; Pop, L.; Bolundut, L.; Tothazan, N.; Borodi, G.; Vida-Simiti, I.; Stefan, R.; Popa, A.; Culea, E.; Pascuta, P.
Abstract: Lead tellurite glass ceramics doped with variable amounts of Gd 3+ ions and co-doped with fixed amounts of silver (Ag2 O or Ag metallic nanoparticles, AgNPs) have been prepared and investigated by X-ray diffraction (XRD), density, electron paramagnetic resonance (EPR) and magnetic susceptibility measurements. The EPR spectra of the studied samples exhibit the typical ''U''-type shape with effective g -values of ≈6, 2.8, 2.0 and a weaker feature at g ≈4.8. At higher contents of Gd 3+ ions the spectral features are broadened and finally are dominated by a broad absorption line located at g ≈2.0 and a weaker feature at g ≈6. The broad EPR line centered at g ≈2.0 is associated to the Gd 3+ ions present predominantly as clustered species. The paramagnetic susceptibility ( χ ) was measured at various temperatures and from the 1/ χ versus T dependence the molar Curie constant ( C M ) and the paramagnetic Curie temperature ( θ p ) have been evaluated. Magnetic susceptibility data show that for low Gd2 O3 contents, x ≤3 mol%, the Gd 3+ ions are randomly distributed in the host glass ceramics matrix and are present only as isolated species. For higher Gd2 O3 contents, x >3 mol%, the Gd 3+ ions appear as both isolated and antiferromagnetically coupled species.